VD_FINDINFO Jug / 2011 / 101 vom 6. Juni 2011 - VD Tribunal cantonal (2011)
MOTIF DE RÉVISION, RÉVISIONDÉCISION, AIASSURANCE, PRESTATION D'ASSURANCEAI | 44 LPGA, 53 al. 1 LPGA, 61 let. g LPGA, 61 let. i LPGA, 100 al. 1 let. b LPA-VD, 101 LPA-VD, 102 LPA-VD, 117 al. 1 LPA-VD, 49 al. 1 LPA-VD, 55 LPA-VD